Investigation of the prevalence of latent tuberculosis in cancer patients compared to non-cancer patients: a case-control study - Mortezazadeh, Masoud; Karimi, Mehdi; Esfandbod, Mohsen; Mofidi, Abbas; Hemmati, Nima; Kashani, Mehdi; Shirsalimi, Niyousha; Seyyed Mahmoudi, Seyyed Taher; Kamali Yazdi, Ehsan (Oncology Reviews, 2024)
Background: Latent tuberculosis (TB) can reactivate in immunocompromised individuals, such as cancer patients undergoing chemotherapy, leading to severe complications. Understanding the prevalence of latent TB in this high-risk group is crucial, especially in regions with moderate to high TB burdens. Aim: This study aims to determine the prevalence of latent tuberculosis in cancer patients before chemotherapy and immunotherapy to guide preventive interventions and reduce the risk of TB reactivation. Methods: This case-control study was conducted at Sina Hospital in Tehran, Iran, from 2012 to 2022. A total of 392, including 107 newly diagnosed cancer (case) and 285 non-cancer (control) patients, were enrolled in this study. All patients had received the Bacillus Calmette-Guérin (BCG) vaccine at the age of one. They underwent a thorough clinical examination and were screened using the tuberculin skin test (TST) to detect latent TB. Any active TB cases were identified through acid-fast smear tests. The data collected from the study participants was then analyzed. Results: The results showed no significant difference in the size of TST between cancer and non-cancer patients (cases: median=2 mm, IQR: 1-12; controls: median = 2 mm, IQR: 1-5; P=0.09). The prevalence of latent TB was 27.1% in cancer patients and 20.7% in non-cancer patients, with no significant association identified between latent TB and malignancies (P-value = 0.176). Over a median follow-up of four years, mortality was significantly higher in cancer patients compared to controls (42.1% vs. 1.8%; P<0.001, OR=40.64). Additionally, deceased patients exhibited a greater prevalence of latent TB (44% vs. 19.3% in survivors; P<0.001, OR=3.28), and increased size of TST was associated with higher mortality risk among cancer patients. Conclusion: In conclusion, this study emphasizes the need for vigilant latent TB screening in cancer patients, given the association between larger TST sizes and increased mortality risk. While no direct link between cancer type and latent TB was found, proactive TB management remains crucial, particularly for those undergoing immunosuppressive therapy.